Quality of Life after Open versus Closed Treatment for Mandibular Condylar Fractures - Samreena,; Alam, Jehan; Shah, Ruqaya; Javeria,; Anosha,; Zulakha, (Indus Journal of Bioscience Research, 2024)
Objective: To compare the quality of life after surgical management with closed reduction and internal fixation (CRIF) versus open reduction and internal fixation (ORIF) for mandibular condylar fractures. Methodology: This analytical observational study was carried out between January 2024 to June 2024, at the Department of Oral and Maxillofacial Surgery, Jinnah Postgraduate Medical Centre, Karachi, focusing on patients with mandibular condylar fractures. The study assessed their quality of life using the General Oral Health Assessment Index (GOHAI) Questionnaire, with scores ranging from 1 to 3, where 1 denoted "Always," 2 indicated "Sometimes," and 3 represented "Never." Quality of life scores were categorized as high (34-36), medium (31-33), or low (